Critical Evaluation of Strategies for the Production of Blood Coagulation Factors in Plant-Based Systems - Top, Oguz; Geisen, Ulrich; Decker, Eva L.; Reski, Ralf (Frontiers in Plant Science, 2019)
The use of plants as alternative production platforms for pharmaceutical proteins has been on the rise for the past two decades. The first marketed plant-made pharmaceutical, taliglucerase alfa against Gaucher`s disease produced in carrot cells by Pfizer/Protalix Biotherapeutics, was approved by the US Food and Drug Administration (FDA) in 2012. Milestones which followed include the successful completion of phase I clinical trial of the HIV-neutralizing human monoclonal antibody 2G12, expressed in Nicotiana tabacum in 2015, and alpha-galactosidase A against Fabry disease produced in Physcomitrella patens in 2017, and the start of phase III efficacy study of the seasonal quadrivalent influenza vaccine manufactured in Nicotiana benthamiana in 2017. The approaches in the field of plant molecular farming are concentrated on the use of different plant species with distinct and overlapping benefits rather than the development of standardized platforms as in microbes and mammalian cells. These benefits might be low cost and highly scalable biomass production compared to the fermentation systems, safety compared with other expression systems, as plant-based systems do not produce endotoxins, and the ability to perform complex eukaryotic post-translational modifications, e.g. N-glycosylation that can be further engineered to achieve humanized N-glycan structures. The necessity of large-scale and less expensive production of human blood coagulation factors, particularly factors associated with rare bleeding disorders may be an important area for plant-based systems, as they do not fit into the industry-favored production models. In this review, we explore previous studies on recombinant production of Factor II, VIII, IX and XIII in different plant species and discuss potential strategies to overcome bottlenecks in plant-based systems. The impact of plant molecular farming in the production of clotting factors will increase once plant-made proteins can compete with products in the market in terms of manufacturing costs and product quality.